Acoustic puncture assist device versus loss of resistance technique for epidural space identification - Amit Kumar Mittal; Nitesh Goel; Itee Chowdhury; Shagun Bhatia Shah; Brijesh Pratap Singh; Pradeep Jakhar (Indian Journal of Anaesthesia, 2016)
Background and Aims: The conventional techniques of epidural space (EDS) identification based on loss of resistance (LOR) have a higher chance of complications, patchy analgesia and epidural failure, which can be minimised by objective confirmation of space before catheter placement. Acoustic puncture assist device (APAD) technique objectively confirms EDS, thus enhancing success, with lesser complications. This study was planned with the objective to evaluate the APAD technique and compare it to LOR technique for EDS identification and its correlation with ultrasound guided EDS depth. Methods: In this prospective study, the lumbar vertebral spaces were scanned by the ultrasound for measuring depth of the EDS and later correlated with procedural depth measured by either of the technique (APAD or LOR). The data were subjected to descriptive statistics; the concordance correlation coefficient and Bland-Altman analysis with 95% confidence limits. Results: Acoustic dip in pitch and descent in pressure tracing on EDS localisation was observed among the patients of APAD group. Analysis of concordance correlation between the ultrasonography (USG) depth and APAD or LOR depth was significant (r ≥ 0.97 in both groups). Bland-Altman analysis revealed a mean difference of 0.171cm in group APAD and 0.154 cm in group LOR. The 95% limits of agreement for the difference between the two measurements were − 0.569 and 0.226 cm in APAD and − 0.530 to 0.222 cm in LOR group. Conclusion: We found APAD to be a precise tool for objective localisation of the EDS, co-relating well with the pre-procedural USG depth of EDS.